(untitled) (Journal of Science and Technology, 2016)
Research has shown that non-conventional factors like housing and residential experiences during childhood have impacts on children’s success. Given the critical importance of human capital accumulation in Ghana, it is significant from policy standpoint to recognise factors and mechanisms that are relevant to the next generation’s educational performance. This paper attempts to identify the impacts of housing tenure and residential moves on the educational performance of children. The research focused on Junior Secondary School (JSS) leavers in Accra. Chronological information of the Pupils during childhood on residential moves and their educational performance between the ages of 12- 17 (JSS level) was collected. The results of the analysis indicate large disparities in educational outcomes between children with different housing tenures and strong residential mobility experiences. Even after taking into consideration a set of rich endogenous factors, a positive home ownership effect and a negative residential moves effect remain with significant magnitudes.